2019
DOI: 10.1080/19476337.2019.1600036
|View full text |Cite
|
Sign up to set email alerts
|

Citrus pectin obtained by ultrasound-assisted extraction: Physicochemical, structural, rheological and functional properties

Abstract: Tangerine (Citrus reticulata. CRP) and grapefruit (Citrus paradisi. CPP) pectins obtained by ultrasound-assisted extraction (UAE) and conventional extraction (CE) using citric acid were characterized to establish their potential uses as an alternative source of commercial pectin. The pectins obtained by UAE and CE presented a pseudoplastic fluid characteristic with shear thinning behavior, a high esterification degree (CRP 82.30-71.81% and CPP 84.25-72.15%) and were of commercial quality based on galacturonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 55 publications
(74 reference statements)
1
31
1
Order By: Relevance
“…However, the report of Eaks and Sinclair [30] revealed that avocado pectin content was very low around 0.7 to 1.5%, which may explain this information scarcity. However, except lemon pectin, pectin yield value of others fruits was below the range (20-30%) reported for commercial pectin from citrus peels [29]. Nevertheless, pectin extraction yields in our study seem to be high compared to those reported in the literature.…”
Section: Pectin Extraction Yield From Different Fruitscontrasting
confidence: 92%
See 3 more Smart Citations
“…However, the report of Eaks and Sinclair [30] revealed that avocado pectin content was very low around 0.7 to 1.5%, which may explain this information scarcity. However, except lemon pectin, pectin yield value of others fruits was below the range (20-30%) reported for commercial pectin from citrus peels [29]. Nevertheless, pectin extraction yields in our study seem to be high compared to those reported in the literature.…”
Section: Pectin Extraction Yield From Different Fruitscontrasting
confidence: 92%
“…Moreover, De Moura, et al [12] reported similar but slightly lower pectin yield (17.96%) from orange pomace. As regards grapefruit, similar trend of pectin yield (15.76%) was reported by Polanco-Lugo, et al [29] using acid extraction method. Furthermore, information on avocado pectin in literature is rare.…”
Section: Pectin Extraction Yield From Different Fruitssupporting
confidence: 85%
See 2 more Smart Citations
“…[52] (Continued) Also, US changes in inter-and intra-molecular interactions would account for either an enhance or decline in texture and AV, antioxidant properties, emulsifying capacity, of a number of polymercontaining systems. [67][68][69][70] The application of ultrasonic process as a unique preservation factor is unable to effectively kill all the microorganisms since the high levels needed could adversely modify nutritional and sensory properties of the juices. This limitation has suggested that US could be more effective when used in combination with other methods such as heat treatment (pasteurization or thermosonication (TS)), supercritical carbon dioxide, pressure, antimicrobial compounds (vanillin, citral benzoate, and citrus extract), organic acids (lactic acid and acetic acid), chitosan, ultraviolet (UV), pulsed electric field and pulsed light for inactivation of some pathogenic and spoilage microorganisms.…”
mentioning
confidence: 99%